La etnografía reflexiva en el campo de la migración del diario de una emigrante: la partida - Guerra Arias, Faiselly (Sociedad y Economía, 2006)
International migratory movements, some of the most relevant current cultural movements, are analyzed in this paper. Abrief reference to the social contexts of migrations is made. The ethnographic exercise on the Colombian migration to Spain shows that the most relevant explanations to leave the country are economic poverty and labor instability.